Applying Dyer's Star Theory to Sport: Understanding the Cultivation of Athlete Stardom - Duncan Samuel (Sciendo, 2022)
Sports stars and heroes have always been a product of the times in which they have existed and, as such, athlete stars, largely constructed by and through the media, have evolved over time. In particular, the meanings of characteristics that have defined stars of different generations have changed as society's expectations and social norms have evolved. This can be understood through Richard Dyer's (1998) star theory, which states that to cultivate their stardom a celebrity must resonate with the ideals, values, and spirit of the time.